2010
DOI: 10.1007/s12253-010-9274-6
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Melting Curve Analysis of DNA Sequence Alterations of Various Sizes

Abstract: In the diagnostic workflow we need to think in algorithms, containing more assays. One of the most important task in the management of cancer patient is to detect nucleic acid sequence changes in clinical specimens. Before using the most expensive method to analyze direct our targets, a screening assay is needed to reduce the number of samples. In the detection of gene-sequence alterations classical screening methods are available, as SSCP, DGGE or TGGE, (Finke Exp Clin Endocrinol Diabetes 104:92-97, 1996; Les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Becságh et al . () reported the successful application of HRM protocols for the detection of DNA sequence alterations of diverse sizes. In this study, we demonstrated the utility of HRM assays to bird sexing in species with a range of sequence variations from 2 bp ( H. pennatus ) to 44 bp ( A. arvensis ).…”
Section: Resultsmentioning
confidence: 99%
“…Becságh et al . () reported the successful application of HRM protocols for the detection of DNA sequence alterations of diverse sizes. In this study, we demonstrated the utility of HRM assays to bird sexing in species with a range of sequence variations from 2 bp ( H. pennatus ) to 44 bp ( A. arvensis ).…”
Section: Resultsmentioning
confidence: 99%